Weight Regain Outcomes in Roux-en-Y Gastric Bypass vs Sleeve Gastrectomy Type of Bariatric Surgery: A Systematic Review and Meta-Analysis pf 13591 Participants - Permata, Angeline Asti Shiela; Halim, Evelyne Naftali; Aditya, Juan; Wibowo, Jeanne Gabrielle; Shantidewi, Shantidewi; Rachman, Manarul Iman Alfafa; Indrianto, Yunita Lestari; Budianto, Aries (JBN (Jurnal Bedah Nasional); Vol 9 No 1 (2025): JBN (Jurnal Bedah Nasional), 2025)
Aim : Bariatric surgery presents a promising option for obesity treatment worldwide; however, the occurrence of weight regain (WR) post-procedure remains a significant concern. Although WR incidence following bariatric surgery has been well established, research looking specifically at particular types of surgery remains scarce. This study aims to investigate WR outcomes following two of the most popular types of bariatric surgery: Roux-en-Y Gastric Bypass (RYGB) and Sleeve Gastrectomy (SG) following substantial weight loss with a minimum 1-year follow-up. Methods : We systematically searched English-language full-text literature from Pubmed, Cochrane, Wiley Library, Proquest, SpringerLink, and ScienceDirect databases from January 2013 to September 2023. This study was registered to PROSPERO (Registration ID: CRD42023468904). Results : A total of 6 eligible good-quality cohort studies of 13591 patients were included in this meta-analysis. Our findings indicate that RYGB type significantly has less WR events compared to SG type of bariatric surgery, revealing an OR of 0.47 (95% CI: 0.34, 0.65, I² = 80%; p < 0.0001). This research may be taken into account when choosing the type of bariatric surgery a patient will undergo in the future. Conclusion : Our meta-analysis demonstrates that patients undergoing SG type of bariatric surgery are more prone to experience WR in comparison to RYGB type. Further research aimed at identifying associated risk factors would contribute significantly to advance our understanding in this domain.